A multi-center, randomized, double-blind, placebo-controlled trial to evaluate the efficacy and safety of Fuzheng Yangxin Granule in treating heart failure with preserved ejection fraction (Qi-Yin deficiency and blood stasis syndrome): study protocol - Chen, Jingjing; Yan, Zian; Wang, Jiacong; Guo, Lijun; Jiang, Zhonghui; Wang, Fangfang; Bai, Ruina; Ma, Xiaochang (Frontiers in Cardiovascular Medicine, 2025)
IntroductionHeart failure with preserved ejection fraction (HFpEF) is a widespread public health issue worldwide. Despite recent advances in pharmacologic treatments and the introduction of new diagnostic approaches, HFpEF remains underdiagnosed and under-recognized in clinical practice. Traditional Chinese medicine (TCM) may offer a potentially effective treatment for HFpEF. Nevertheless, few clinical trials employ rigorous research methodologies to evaluate the efficacy and safety of TCM in treating HFpEF. Consequently, we propose to assess the hypothesis that patients with HFpEF may benefit from Fuzheng Yangxin Granule (FZYX) and evaluate its safety in a rigorously designed clinical trial.MethodsThis multicenter, double-blind, randomized controlled trial will be conducted across seven tertiary hospitals in China. We will enroll 150 participants aged 18–80 years with confirmed HFpEF (Qi-Yin deficiency and blood stasis syndrome) meeting inclusion criteria. Participants will be randomly assigned (1:1) to the FZYX group or the placebo group, ​with both groups receiving standardized Western medical therapy according to the National Heart Failure Guideline 2023. The 12-week intervention phase will be followed by 40-week safety follow-up. The primary outcome will be maximal peak oxygen uptake (peak VO2). Secondary outcomes will include composite endpoint events, all-cause mortality, 6-minute walking distance (6MWD), New York Heart Association (NYHA) functional class, serum N-terminal pro-B-type natriuretic peptide (NT-proBNP), echocardiographic variables, Minnesota Living with Heart Failure Questionnaire (MLHFQ) score, TCM syndrome scores, and the FRAIL scale.DiscussionThe objective of this study is to evaluate the efficacy and safety of FZYX in treating HFpEF (Qi-Yin deficiency and blood stasis syndrome), thereby providing a high-quality, reliable evidence-based foundation for clinical practice.Clinical Trial RegistrationChina Clinical Trial Registry (ChiCTR2400087293), Registered on July 24, 2024.